Epidemiology of sickle cell disease in Saudi Arabia - Jastaniah, Wasil (Medknow Publications, 2011)
Sickle cell disease (SCD) is an autosomal recessive disorder characterized by production of abnormal hemoglobin S and is associated with high morbidity and mortality. Information about the prevalence of SCD in Saudi Arabia is patchy and probably underestimated, but studies have reported that SCD is a relatively common genetic disorder in this part of the world. The prevalence of SCD in Saudi Arabia varies significantly in different parts of the country, with the highest prevalence is in the Eastern province, followed by the southwestern provinces. The reported prevalence for sickle-cell trait ranges from 2% to 27%, and up to 2.6% will have SCD in some areas. Clinical and hematological variability exists in SCD in Saudi Arabia with two major phenotypes: a mild phenotype and a severe phenotype. Further studies on the prevalence, molecular and clinical epidemiology of SCD may help predict disease severity and risk stratification of patients to determine whether to receive early intensive care or continued symptomatic care.